2021
DOI: 10.1136/bmjopen-2021-049095
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Australian primary healthcare nurses in using telehealth during COVID-19: a qualitative study

Abstract: ObjectiveThis study sought to explore the experiences of Australian primary healthcare (PHC) nurses in the use of telehealth during COVID-19. Telehealth was defined as the use of any telecommunications mode (eg, telephone and videoconferencing) to deliver healthcare.Design and settingThematic analysis of qualitative interviews undertaken in Australian PHC.ParticipantsTwenty-five PHC nurses who had participated in a national survey about their experiences during COVID-19 were recruited using purposive sampling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 20 publications
3
96
0
4
Order By: Relevance
“…30 This supports the current study findings regarding the ways GPs adapted their practice to deliver telehealth during COVID-19. The need to refine logistical processes to improve telehealth delivery has been continuously reported in the literature, 11,25,[30][31][32][33] which supports GP discussions on the need for improved infrastructure and streamlined telehealth processes.…”
Section: Strengths and Limitationsmentioning
confidence: 59%
See 2 more Smart Citations
“…30 This supports the current study findings regarding the ways GPs adapted their practice to deliver telehealth during COVID-19. The need to refine logistical processes to improve telehealth delivery has been continuously reported in the literature, 11,25,[30][31][32][33] which supports GP discussions on the need for improved infrastructure and streamlined telehealth processes.…”
Section: Strengths and Limitationsmentioning
confidence: 59%
“…Further to this, timepressures and business needs within general practice have been identified in other research as factors that influence GP service delivery. 25,[27][28][29] In the current study, financial and business pressures were also found to influence GP delivery of telehealth.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper reports specifically on interview data that emerged about perceptions of risk associated with the pandemic. Other disparate aspects of data from the project are reported elsewhere (Halcomb et al, 2020a(Halcomb et al, , 2020bJames et al, 2021).…”
Section: Designmentioning
confidence: 99%
“…There is a substantial volume of international qualitative literature documenting nurses’ experiences of the pandemic. Most of these studies are set in hospitals 25 26 28–36. Fewer studies focus on primary care nurses who, with differing responsibilities during the pandemic and moving forward, possess different insights.…”
Section: Introductionmentioning
confidence: 99%